A UML profile to model classifier refinements - Correa, Natalia (2005)
The refinement technique allows us to capture the relationship between specification and implementation in software developments. The precise documentation of the refinement relations hip makes it possible the traceability of the requirements through the refinement steps. Unfortunately, the standard modelling language UML suffers from a lack of notation to specify complex cases of refinement, which hinders the traceability activities. In this article we present a profile of UML to model Classifier refinements as a composition of elementary refinements, allowing for a more precise syntactical specification of the refinement relationship